2022
DOI: 10.1292/jvms.21-0608
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of avian paramyxoviruses isolated from wild birds and domestic poultry in Taiwan between 2009 and 2020

Abstract: Avian paramyxoviruses (APMVs) belonging to the subfamily Avulavirinae within the family Paramyxoviridae. APMVs consist of twenty-two known species and are constantly isolated from a wide variety of avian species around the world. In this study, the APMV isolates obtained from wild birds and domestic poultry during 2009-2020 in Taiwan were genetically characterized by phylogenetic analysis of their complete fusion protein gene or full-length genome. As a result, 57APMV isolates belonging to seven different spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Additionally, it has been demonstrated that some PPMV-1 isolates may even increase virulence after sequential passaging in chickens ( Abolnik et al, 2004 ). Although previous studies have shown that PPMV-1 can be detected in resident free-ranging pigeons, doves, and magpies in Taiwan ( Liu et al, 2020 , 2022 ), the prevalence of PPMV-1 in wild fields remains unknown. However, our findings proved that PPMV-1 could infect oriental turtle doves, which have an overlapping habitat with pigeons and are widely distributed in Taiwan and other countries in East Asia; thus, the potential threats of PPMV-1 in the poultry industry as well as in animals might be underestimated.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, it has been demonstrated that some PPMV-1 isolates may even increase virulence after sequential passaging in chickens ( Abolnik et al, 2004 ). Although previous studies have shown that PPMV-1 can be detected in resident free-ranging pigeons, doves, and magpies in Taiwan ( Liu et al, 2020 , 2022 ), the prevalence of PPMV-1 in wild fields remains unknown. However, our findings proved that PPMV-1 could infect oriental turtle doves, which have an overlapping habitat with pigeons and are widely distributed in Taiwan and other countries in East Asia; thus, the potential threats of PPMV-1 in the poultry industry as well as in animals might be underestimated.…”
Section: Discussionmentioning
confidence: 96%
“…Newcastle disease virus ( NDV ) is a widespread worldwide virus that not only causes severe endemic outbreaks leading to tremendous economic losses in the poultry industry but also poses a threat to poultry breeders and farmers due to its zoonotic potential ( Gogoi et al, 2017 ). Hemagglutination inhibition ( HI ) and neuraminidase inhibition ( NI ) assays have demonstrated that there are at least 21 species of avian paramyxoviruses ( APMVs ) that can infect up to 250 different avian species ( Gogoi et al, 2017 ; Kuhn et al, 2020 ; Liu et al, 2022 ). In 2019, the International Committee on Taxonomy of Viruses ( ICTV ) officially renamed NDV as avian paramyxovirus-1 ( APMV-1 ), which belongs to the species Avian orthoavulavirus 1 , genus Orthoavulavirus , family Paramyxoviridae , and order Mononegavirales ( Amarasinghe et al, 2019 ; Kuhn et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The isolation rate was 0.35% (5 out of 1438) and 0.21% (3 out of 1438), respectively. APMV-4 and APMV-6 are often detected during AIV monitoring in wild waterfowl in various regions of the world, including some neighboring the Caspian Sea [ 44 , 45 , 46 ]. It is currently unknown what role they play in the ecology of other viruses (for example AIVs).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the two NDVs from wild birds were classified as avirulent as they possessed amino acid sequence motif 112 ERQER|L 117 , which is typical of avirulent strains. Moreover, several studies have also reported the isolation of virulent strains of NDV in chickens [ 44 , 45 , 46 ] and avirulent strains in wild birds [ 33 , 46 , 47 ]. While this study reported avirulent variants of NDV in wild birds, virulent class II variants responsible for many outbreaks have also been isolated in wild birds [ 3 , 48 ], indicating the importance of these birds in disseminating the virus.…”
Section: Discussionmentioning
confidence: 99%